OXIDATION OF VARIOUS CELLULOSE CONTAINING MATERIALS USING THE HNO₃/H₃PO₄–NaNO₂ SYSTEM - Khabibullaev, Jakhongir; Shomurotov, Shavkat (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The oxidation of cellulose-containing materials is an important approach for producing functional derivatives with biomedical applications. In this study, the oxidation behavior of cotton cellulose, medical gauze, and viscose fabric was systematically investigated using an HNO₃/H₃PO₄–NaNO₂ oxidizing system. The effects of oxidizing mixture composition, sodium nitrite concentration, reaction temperature, and reaction duration on the degree of oxidation (DO), oxidation rate, and product yield were evaluated. The results demonstrated that increasing the content of orthophosphoric acid significantly enhanced the DO of the obtained products due to improved fiber swelling and increased accessibility of reactive hydroxyl groups. An optimal NaNO₂ concentration of 1.4% was identified, providing maximum oxidation efficiency through increased formation of nitrogen dioxide in the reaction medium. The oxidation rate was highest during the initial stages of the reaction (1–6 h) and gradually decreased with time as the concentration of oxidizing species diminished. Elevated temperatures and prolonged reaction times led to higher DO values but caused a reduction in product yield due to polymer chain degradation. Comparative analysis revealed that viscose fabric exhibited the highest reactivity, while cotton cellulose showed the lowest oxidation rate under identical conditions, which was attributed to differences in crystalline structure and amorphous content. Overall, the HNO₃/H₃PO₄–NaNO₂ system proved to be an efficient and selective method for obtaining monocarboxylated cellulose with high degrees of oxidation, provided that the reaction parameters are carefully optimized.